Identification of the novel HLA‐B allele, HLA‐B*39:42, in a Chinese individual. Issue 6 (14th March 2013) - Ni, L.; Shan, X.; Wang, L.; Zhixin, Z.; Gong, Z.
<x xml:space="preserve">Abstract</x> The HLA‐B*39:42 allele differs from the closest matching allele B*39:01:01:01 by two nucleotide substitutions in exon 3.